2021
DOI: 10.1101/2021.03.02.433513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decline in large-seeded species in Danish grasslands over an eight-year period

Abstract: The historic land-use changes in grassland habitats may have lead to community level selection on seed mass as a response to the environmental changes. A time-series analysis of Danish grassland pin-point plant cover data from an eight-year period was carried out to investigate such a selection response. Across four grassland habitat types, community selection towards lighter seeds was observed during the eight-year period, but generally only limited trait selection was observed on seed mass. The mostly negati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…These previous observations of grassland vegetation change are further corroborated by this study, since the relative proportion of plant species with a Grime C strategy was found to increase relative to plant species with a Grime R strategy. Moreover, and possibly also a selection response to these environmental changes, a significant community selection towards lighter seeds (Damgaard, 2021b) and against insect pollinated plants ( Ehlers et al, 2021) has been observed in Danish grasslands.…”
Section: Tablementioning
confidence: 99%
“…These previous observations of grassland vegetation change are further corroborated by this study, since the relative proportion of plant species with a Grime C strategy was found to increase relative to plant species with a Grime R strategy. Moreover, and possibly also a selection response to these environmental changes, a significant community selection towards lighter seeds (Damgaard, 2021b) and against insect pollinated plants ( Ehlers et al, 2021) has been observed in Danish grasslands.…”
Section: Tablementioning
confidence: 99%